Why do patients struggle with their medicines?-A phenomenological hermeneutical study of how patients experience medicines in their everyday lives. - Joanne M Fuller (Public Library of Science (PLoS), 2021)
Why do so many people struggle with their medicines despite decades of research on medicines taking? Research into how people experience medicines in their everyday life remains scarce with the majority of research in this area of focusing on whether or not people take their medicines as prescribed. Hence, this study used a phenomenological hermeneutical qualitative design to gain a deeper understanding of individuals' perspectives on the lived experience of medicine-taking. Findings from this study highlight five main themes where participants experience medicines as: 1) life-saving and indispensable, 2) normal and a daily routine, 3) confusing and concerning, 4) unsuitable without adjustment, and 5) intrusive and unwelcome. These results can be the basis for mutually agreed prescribing through a co-creative approach that aims at enhancing open and honest dialogues between patients and healthcare professionals in partnership about medicines.